Upaya Rehabilitasi Sosial Dalam Penanganan Gelandangan dan Pengemis Di Provinsi Dki Jakarta - Marlinda, Astrini; Hati, Getar (UI Scholars Hub, 2015)
This article discusses about the social rehabilitation efforts in handling the homeless and beggars in Jakarta at Panti sosial Bina Insani (PSBI BD 2) Cipayung. Researcher conducting a qualitative descriptive on this study.The findings from this research show that social rehabilitation efforts in homeshelter is not maximized so that the homeless people and beggars in Jakarta tends to return to the street after getting coaching in this homeshalter. This research provide a recommendation to the government to provide a homeshalter which focused for homeless and beggars social rehabilitation, give strict punishment to the homeless and beggars who are back on the street and increases quality and quantity of human resourcesservant.